Wet and dry corn yield under intercrop culivation with marandu grass and/or dwarf pigeon pea and nutritional value of the marandu grass in succession - Garcia, Cássia Maria de Paula [UNESP]; Costa, Ciniro [UNESP]; Meirelles, Paulo Roberto de Lima [UNESP]; Andreotti, Marcelo [UNESP]; Pariz, Cristiano Magalhães [UNESP]; Freitas, Leandro Alves [UNESP]; Filho, Marcelo Carvalho Minhoto Teixeira [UNESP] (Southern Cross Publishing, 2016)
The aim of this study was to evaluate corn grain yield and dry matter yield and nutritional value of Urochloa brizantha cv. Marandu (marandu grass) in succession to an intercrop of corn with marandu grass and/or dwarf pigeon pea (Cajanus cajan cv. Anão) in a dryland area. The experiment was conducted during the crop years of 2013/14 and 2014/15, in a low-altitude Cerrado biome (savannah) experimental area. The experiment was set up as a randomized block design with six replications, in a 2 × 2 × 2 factorial arrangement consisting of two intercrops [corn with marandu grass (CB) and corn with marandu grass and dwarf pigeon pea (CBP)]; two grain harvest times (wet and dry grain stages); and two consecutive years (2013/14 and 2014/15). Irrespective of the intercrop, the harvest of corn grain in the wet stage for silage minimized the losses caused by climatic factors. The intercrop of corn with marandu grass and dwarf pigeon pea reduced the yield of wet corn grains and the dry matter of the marandu grass in succession. Marandu grass in succession to the intercrop of corn with dwarf pigeon pea resulted in better nutritional value because of the lower fiber and higher total digestible nutrients contents.
Keywords: Cajanus cajan; Cerrado; Pastures; Urochloa brizantha; Zea mays